Lumbar Degenerative Disc Disease: Current and Future Concepts of Diagnosis and Management. (2nd April 2012) - Taher, Fadi; Essig, David; Lebl, Darren R.; Hughes, Alexander P.; Sama, Andrew A.; Cammisa, Frank P.; Girardi, Federico P.
Abstract : Low back pain as a result of degenerative disc disease imparts a large socioeconomic impact on the health care system. Traditional concepts for treatment of lumbar disc degeneration have aimed at symptomatic relief by limiting motion in the lumbar spine, but novel treatment strategies involving stem cells, growth factors, and gene therapy have the theoretical potential to prevent, slow, or even reverse disc degeneration. Understanding the pathophysiological basis of disc degeneration is essential for the development of treatment strategies that target the underlying mechanisms of disc degeneration rather than the downstream symptom of pain. Such strategies ideally aim to induce disc regeneration or to replace the degenerated disc. However, at present, treatment options for degenerative disc disease remain suboptimal, and development and outcomes of novel treatment options currently have to be considered unpredictable.